Design of Monitoring and Control System Temperature Based on IoT for Egg Incubator Using Solar Panels - Mutaqim, Rendi; Zulkarnaen, Indah Gita Gayatri; Wulandari, Rindi (CV. Literasi Indonesia, 2024)
Energy is one of the most important components of human life. In the livestock industry, problems occur when there is a power outage so that the incubator cannot function. Solar energy is one of the renewable energy sources that convert solar radiation into electricity based on the photovoltaic effect and can be a solution to the above problems. In addition, another problem is that the egg incubator used by farmers still uses a manual system, the solution to the problem by utilizing IoT technology for monitoring and control systems for temperature, humidity, and egg rotation. the purpose of the research is to develop a smart incubator system to automate IoT-based temperature, humidity, and egg rotation systems so that they can be monitored more effectively using solar power as a power source. This research uses observational and quantitative methods with data collection techniques carried out through observation. The result of this research is the design of an IoT-based automatic incubator system using 30 WP solar panels as an energy source. In the measurement of the temperature monitoring IoT system in real-time, an error value of 0.93 was obtained with a temperature accuracy value of 99.07 which was declared very good, in the blynk test with a thermometer an error value of 2.92 was obtained with an accuracy value of 97.08 which was declared very good, in the humidity test an error value of 6.9 was obtained with an accuracy value of 93.1 which was declared quite good.